Online and Offline Behavior: Two Realities or One? - Bovina I.B; Dvoryanchikov N.V (Moscow State University of Psychology and Education, 2020)
The paper focuses on a social psychological analysis of the effects of new technologies on the individual and his/her social experience. Among the impacts of social media on everyday life are the transformation and simplification of communication process, as well as the transformation of power relations and norms associated with this process. Participants of communication process have various opportunities to maintain anonymity, to construct and modify identities, and to interrupt and or even to terminate communication process at any time. The literature review reveals the negative side of the Internet use and demonstrates antinormative phenomena. The explanations of aggressive online behaviour, as well as the attempts to predict offline behaviour from online observations, are based on a wide range of interindividual constructs. However, these studies are mostly descriptive. The paper highlights the potential of social psychological knowledge (social cognitive theory, social representations theory and deindividuation theory) to answer the question about the relationship of online and offline behaviour. The theory of social representations may also be of much use in creating prevention programmes for adolescents and young people.